PERAN SMART TV SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MATA PELAJARAN PAI DI SMK DIPONEGORO KARANGANYAR PEKALONGAN - Fahmi Agil; Arditya Prayogi; Miftakhudin Miftakhudin (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This research examines the function of Smart TV technology as an interactive instructional medium within Islamic Religious Education (PAI) courses at SMK Diponegoro Karanganyar Pekalongan. The study was prompted by persistent challenges in PAI classrooms, where student enthusiasm and active involvement remained limited due to the dominance of teacher-centered, lecture-based instruction. A descriptive qualitative methodology was employed, gathering data through classroom observation, semi-structured in-depth interviews, and document review. Participants in this study included two PAI instructors, thirty students from grades X and XI representing diverse vocational programs, the school principal, and the vice-principal for curriculum affairs. Findings indicate that Smart TV integration substantially elevated student engagement across behavioral, cognitive, and emotional dimensions. The technology facilitated rich multimedia delivery of Islamic content—including Quranic verse visualization, digital documentary screenings, and real-time mirroring of student work—thereby enabling meaningful, enjoyable, and contemplative learning experiences. The study concludes that Smart TV functions not merely as an instructional aid, but as a transformative agent reshaping the pedagogical culture of PAI toward active, technology-enriched participation. It is recommended that schools formally embed Smart TV use within PAI curriculum planning frameworks to ensure systematic and sustained implementation